Human helminthes intestinal parasites of Morang district, Nepal - Yadav, Shiv Narayan (Nepalese Journal of Biosciences, 2013)
The present studyy examined association between ABO human blood group and helminth parasites. In total 3000 people were investigated and 1300 individuals were found infected with helminth parasites, namely Ascaris lumbricoides (52.46%) Ancylostoma duodenale (45.00%), Trichuris trichura (1.90%), Enterobius vermicularis (0.03%), Taenia solium (0.015%), Hymenolepis nana (0.15%).